(untitled) - Fisher, Douglas (Newark, 2012)
This book focuses on the quantitative and qualitative factors of text complexity as well as the ways in which readers can be matched with texts and tasks. It also examines how close readings of complex texts scaffold students understanding and allow them to develop the skills necessary to read like a detective. The International Reading Association is the world's premier organization of literacy professionals. Our titles promote reading by providing professional development to continuously advance the quality of literacy instruction and research.
Keywords: Reading comprehension,Đọc hiểu; Study and teaching (Elementary),Dạy và học (Cơ bản); United States,Hoa Kỳ